The inverse function of h(x) is given by:
[tex]h^{-1}(x) = -\frac{5x}{3} + \frac{5}{6}[/tex]
How to find the inverse of a function h(x)?
Suppose that we have a function y = h(x). To find the inverse, we exchange x and y, and then isolate y.
In this problem, the function is given by:
y = -3/5x + 1/2.
Exchanging x and y, we have that:
x = -3/5y + 1/2.
Now we do the operations to isolate y, hence:
3/5y = 1/2 - x
3y = 5/2 - 5x
y = 5/6 - 5x/3.
Hence the inverse function is given by:
[tex]h^{-1}(x) = -\frac{5x}{3} + \frac{5}{6}[/tex]
More can be learned about inverse functions at https://brainly.com/question/8824268
#SPJ1